Konstruksi Musikal Sekar Anyar dalam Tembang Sunda Cianjuran: Analisis Struktur Dongkari dan Formula Ornamen pada Lagu “Wegah”-“Sajeroning Sindang” - Dika Dzikriawan; Wiwik Sushartami; Aton Rustandi Mulyana (Jurnal Kajian Seni, 2021)
ABSTRACTSekar anyar is tembang sunda cianjuran innovation who created by Ubun Kubarsah. The term of serkar anyar in tembang sunda cianjuran first appeared in the XIX Pasanggiri Tembang sunda cianjuran (PTSC) Daya Mahasiswa Sunda (DAMAS) that goes on Graha Sanusi Universitas Padjadjaran (UNPAD) Bandung in December 2009. During this time, sekar anyar in tembang sunda cianjuran is still a debate among the tembang sunda cianjuran community. The discourse that appears in the sekar anyar is basically debating about the terminology itself, the problem of characteristics (in this case, the issue of musical and non-musical), the issue of character assassination, to the issue of whether sekar anyar is fit to be included in the category of the tembang sunda cianjuran genre. The following resarch aims to explain how the musical construction of sekar anyar in the tembang sunda cianjuran from the perspective of using the dongkari structure and the formula ornamen in the song "Wegah" - "Sajeroning Sindang".This research employs the ethnographic method with the theoretical framework of Bruno Nettl's selective approach to musical descriptions. The average use of dongkari and the use of ornaments in the sekar anyar song tends to be minimal. The lack of dongkari and ornamentation in the sekar anyar greatly influenced the achievement of the nuances of character that usually apply to tembang sunda cianjuran. ABSTRAKSekar anyarmerupakan karya inovasi dalam tembang sunda cianjuranyang digagas oleh Ubun Kubarsah. Istilah sekar anyardalam tembang sunda cianjuranpertama kali muncul pada Pasanggiri Tembang Sunda Cianjuran(PTSC) Daya Mahasiswa Sunda (DAMAS) ke-XIX yang berlangsung di gedung Graha Sanusi Universitas Padjadjaran (UNPAD) Bandung pada bulan Desember 2009. Keberadaan sekar anyardalam tembang sunda cianjuranhingga saat ini masih menjadi perdebatan di kalangan masyarakat tembang sunda cianjuran. Wacana yang muncul pada fenomena sekar anyarpada dasarnya memperdebatkan soal peristilahannya itu sendiri, masalah ciri-ciri mandiri (dalam hal ini adalah persoalan musikal dan non musikal), issue pembunuhan karakter, sampai pada persoalan apakah laik sekar anyardimasukkan ke dalam kategori genre tembang sunda cianjuran. Penelitian ini difokuskan untuk melihat bagaimana konstruksi musikal sekar anyardalam tembang sunda cianjurandari perspektif penggunaan struktur dongkaridan formula ornamen pada lagu “Wegah”-“Sajeroning Sindang”. Penelitian dilakukan menggunakan metode etnografi dengan kerangka teori pendekatan selektif deskripsi musikal Bruno Nettl. Hasil yang didapatkan rata-rata penggunaan dongkaridan penggunaan ornamen pada lagu sekar anyarcenderung minim. Minimnya dongkaridan ornamen pada sekar anyarsangat berpengaruh terhadap pencapaian nuansa karakter yang biasa berlaku pada lagu-lagu tembang sunda cianjuran.